Syphilis of fungal world: Novel skin manifestations of histoplasmosis in an immunocompetent host - Khader Anza; George Mamatha; George Sandhya; Rajan Uma; Kunnummal Muhammed (Wolters Kluwer Medknow Publications, 2012)
A case of chronic disseminated cutaneous histoplasmosis with unusual skin manifestations in an immunocompetent host is reported. Presence of cutaneous ulcers, linear erythematous plaques, skin coloured atrophic plaques and recurrent self-limiting oral ulcers in a single patient has not been documented in literature so far. Diagnosis was established by identifying small intracellular yeast-like cells of Histoplasma in tissue smear and skin biopsy. Leishman stained tissue smear proves to be an easy and simple procedure for diagnosis of histoplasmosis.